The effect of interventions aimed at improving participation outcomes for children with disabilities: a systematic review. (24th May 2015) - Adair, Brooke; Ullenhag, Anna; Keen, Deb; Granlund, Mats; Imms, Christine
Abstract : Aim: Enhancement of participation has been described as the ultimate outcome for health and educational interventions. The goal of this systematic review was to identify and critically appraise studies that aimed to improve the participation outcomes of children with disabilities. Method: Nine databases that index literature from the fields of health, psychology, and education were searched to retrieve information on research conducted with children with disabilities aged between 5 years and 18 years. Articles were included if the author(s) reported that participation was an intended outcome of the intervention. The articles included were limited to those reporting high‐level primary research, as defined by Australia's National Health and Medical Research Council evidence hierarchy guidelines. No restrictions were placed on the type of intervention being investigated. Results: Seven randomized controlled or pseudo‐randomized studies were included. Only three of these studies identified participation as a primary outcome. Both individualized and group‐based approaches to enhancing participation outcomes appeared to be effective. Studies of interventions with a primary focus on body function or activity level outcomes did not demonstrate an effect on participation outcomes. Intepretation: Few intervention studies have focused on participation as a primary outcome measure. Approaches using individually tailored education and mentoring programmes were found to enhance participation outcomes, while exercise programmes, where participation was a secondary outcome, generally demonstrated little effect. What this paper adds: Individually tailored education and mentoring programmes can enhance participation outcomes. Programmes targeting primary participation outcomes were most effective. Clarity is needed regarding the definition of participation.